Modified Dust-Lower-Hybrid Waves in Quantum Plasma - Abdul Rauf; I. Zeba; Muhammad Saqlain (Scientific Inquiry and Review, 2018)
Dust-lower-hybrid waves in quantum plasma have been studied. The dispersion relation of the dust-lower-hybrid wave has been examined using the quantum hydrodynamic model of plasma in an ultra-cold Fermi dusty plasma in the presence of a uniform external magnetic field. Graphical analysis shows that the electron Fermi temperature effect and the quantum corrections give rise to significant effects on the dust-lower-hybrid wave of the magnetized quantum dusty plasma.